Selected factors influencing the risk of falls in the elderly - Wróblewska, Izabela; Wróblewska, Zuzanna; Bujak-Rogala, Elżbieta; Manulik, Stanisław; Sobieszczańska, Małgorzata (Journal of Education, Health and Sport, 2019)
Introduction: Falls concern 1/3 of people aged >65 years and every second person aged >80, leading to seniors’ disability and dependence on other people’s care. The unmodifiable causes for falls are age, sex, marital status, and place of residence. The modifiable causes include involutional changes in all body systems, multimorbidity, polypharmacy, as well as living and environmental conditions. Aim: To determine the risk factors of falls in the elderly. Material and methods: The study involved 220 hospitalized patients aged >65 years who had experienced a fall. An anonymous questionnaire was applied that referred to the medications taken, diagnosed diseases, factors predisposing to falls, and the frequency of falls. The Mini-Mental State Examination was performed to qualify the subjects, and Tinetti test to assess gait and balance. Results: In the Tinetti scale, 48.2% of the subjects were characterized by a rise in the risk of fall 5-fold higher than average; the risk increase less frequently concerned people undertaking physical activity and those who were younger (65–70 years) (P<0.05). The Tinetti test analysis revealed a statistically significant relation (P˂0.05) between brain stroke, Parkinson’s disease, orthostatic hypotonia, gait disorders, and falls. The decrease in the number of falls was influenced neither by dizziness, declared by 70.4% of the patients (P=0.092), nor by the number of medications taken (P=0.072). It was influenced, however, by the usage of orthopedic equipment (P˂0.001). Conclusion: The risk of falls in the elderly rises with age. Physical activity decreases the risk; it is increased, though, by gait and balance disorders, Parkinson’s disease, past brain stroke, and orthostatic hypotonia.